L' immaginazione di Gesù: William Blake, Oscar Wilde e gli altri. - Saracino, Francesco (2025)
After having been neglected for a long time, the imagination of Jesus became a topic that fascinated artists, writers and theologians, especially in the Anglo-Saxon world, during the 19th century. These pages outline the phenomenon by referring to some of the protagonists of that turning point.